Lexical Landscape of Climate Change Discourse in Bangladeshi National Newspapers: A Corpus Linguistic Analysis - Hasan Shaikh; Dr. Md. Obaidullah (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2026)
As climate vulnerability intensifies and environmental debates become increasingly politicized, Bangladeshi national newspapers assume a pivotal role as discursive arenas where climate change is articulated through the socio-political idioms of the nation-state. To investigate how this articulation takes shape, the study applies corpus linguistic methods to a purposefully compiled dataset comprising nearly 350 opinion essays and news reports, amounting to approximately 400,000 tokens, published across three leading Bangla dailies between 2020 and 2025. The analysis reveals a hybridized discursive framework in which scientific credibility is interwoven with emotive resonance, temporal urgency, and developmental-nationalist logic. Rather than foregrounding global mitigation policies, newspapers localize the discourse centering lived vulnerability, infrastructural resilience, and collective agency to foster a participatory, if elite-mediated, climate consciousness. Keyword and concordance patterns further expose an economic framing that underscores aid dependency, financial risk, and global injustice, while simultaneously promoting Bangladesh as a resilient, technologically optimistic, and morally authoritative actor. The discourse privileges policy and academic voices, often marginalizing grassroots and ecological perspectives in favor of narratives that align with neoliberal development agendas. Ultimately, the study argues that Bangladeshi media reconfigures climate change as both an existential peril and a developmental opportunity functioning less as neutral chroniclers and more as discursive architects of a climate-resilient nationalism embedded in global political ecologies.